PENDIDIKAN AKHLAK DALAM PERSPEKTIF HAMKA (Studi Q.S. Luqman dalam Tafsir Al-Azhar) - Achyar Zein, Syamsu Nahar, Abdullah Sani Ritonga, (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2018)
Abstract: Islamic education is education that originates from the Koran. Interpretation is a description of scholars regarding the content and value of the Quran. Based on these two things, this study aims to issue elements regarding moral education based on Hamkas description in the book entitled Tafsir Al-Azhar. The elements in question are understanding of moral education, its purpose, method of implementation, moral resources, moral education material, and moral education components. Through library research and the maudhÅ«i method initiated by Shaykh Mahmud Syaltut, it was found that the definition of moral education according to Hamka is education that directs human morals to the true aqeedah, the right attitude, the right way of caring, always doing the right thing, and being civilized and correct manners. The purpose of moral education is to direct the behavior of students to those in understanding. The method of implementation is lectures, demonstrations, and examples. Moral sources are from Allah, the guide of the Messenger of Allah, and the attitude of the community around the students. Moral education material is not shirk, prayer, patience, follow the procedure, respect for parents if parents call on the truth, associate parents properly if people call on polytheism, amar maruf nahi mungkar, do not look away when talking, do not be arrogant in behave, dont be proud of yourself in life, simple in walking and soft in speaking according to the context. The moral education component consists of educators, students and education evaluation. In this study also described the relevance of moral education in Hamkas perspective on education today, especially character education. It was found that there was a real relevance between moral education and character education. The relevance is in the sense and purpose of producing good learners, with good definitions that differ between the two: good according to moral education is good in religious review, while good according to character education is good in the review of Pancasila as the principle of the state. Likewise in other elements. With this relevance, it was concluded that there was actually no conflict between the two but rather moral education complemented things that had not been formulated by character education.Â Keywords: Tafsir Al-Azhar, Hamka, Moral Education, Character Building Education